Strong Madrasah Education Management Strategy To Improve The Quality of Education In MTsn 2 Malang City - Widodo, Wahyudi (Pelopor Publikasi Akademika, 2024)
Madrasah is a formal educational institution that has an important role in educating the nation's life. The quality of madrasa education needs to be continuously improved so that madrasas can play an optimal role in educating the nation's life. One effort that can be made to improve the quality of madrasa education is to implement strong madrasa education management. The aim of this research is to determine a strong madrasa education management strategy to improve the quality of education at MTSN 2 Malang City. This study used qualitative research methods. Data collection techniques in this research were carried out using literature study and observation. The collected data is then analyzed in three stages, namely reduction, data presentation and drawing conclusions. The research results show that strong madrasa education management is an important step in improving the quality of madrasa education. This step is carried out by implementing a good work ethic and performance, so that it can fulfill the mandate of Law no. 20 of 2003 concerning the National Education System. Apart from that, education management strategies can be implemented through implementing Allah SWT's command to print 'ulul albab' and Rasulullah SAW's command